2014
DOI: 10.1016/j.juro.2013.12.031
|View full text |Cite
|
Sign up to set email alerts
|

Urological Symptoms in a Subset of Patients with Urological Chronic Pelvic Pain Syndrome and a Polysymptomatic, Polysyndromic Pattern of Presentation

Abstract: Purpose To characterize the urologic symptoms of a subset of urologic chronic pelvic pain syndrome (UCPPS) patients who have both a high somatic symptom burden and a wide symptom distribution fitting a “poly-symptomatic, poly-syndromic” (PSPS) pattern of presentation. Materials and Methods 81 UCPPS patients enrolled in the NIDDK MAPP Research Network Study at the Washington University in St. Louis and the University of Alabama at Birmingham sites completed a symptom questionnaire to assess their somatic symp… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
15
0

Year Published

2015
2015
2022
2022

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 16 publications
(15 citation statements)
references
References 22 publications
0
15
0
Order By: Relevance
“…Gender was also shown to impact symptom presentation, although these results are mixed. Women are more likely to present with polysymptomatic complaints . The examination of abuse prevalence has occurred predominately in females.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Gender was also shown to impact symptom presentation, although these results are mixed. Women are more likely to present with polysymptomatic complaints . The examination of abuse prevalence has occurred predominately in females.…”
Section: Resultsmentioning
confidence: 99%
“…Women are more likely to present with polysymptomatic complaints. 9,23,34 The examination of abuse prevalence has occurred predominately in females. In the most comprehensive psychological study to date, comparing gender, Naliboff et al 9 found that women are more likely to report early life and adult trauma exposure, greater helplessness, and poorer functionality than men-irrespective of symptom severity or age.…”
Section: Demographic Factorsmentioning
confidence: 99%
“…The PSPS-Q has been utilized in two previous studies to characterize systemic symptoms in patients with IC/BPS. 10, 11 For this and previous studies, 10, 11 widespread systemic symptoms were operationalized as having ≥25 symptoms in ≥9 symptom groups in women, or ≥20 symptoms in ≥8 symptom groups in men. The operational definition was different between men and women because men do not have gynecological symptoms.…”
Section: Methodsmentioning
confidence: 99%
“…With all thefindings on immunological and metabolic parameters from various scientific literature being combined in a single table (see Table 1), it can be seen that the following parameters were the key parameters of the standard formula of the immune system disorders in acute cystitis: T cytotoxic , Ig M, MWM, all with a stimulating vector of the 3 rd degree. Chronic cystitis was characterized by a decrease in the number of T-helpers, IgA with the accumulation of pro-inflammatory interleukin 8 (Lai et al 2014). The complication of chronic cystitis with chronic pyelonephritis resulted in leukocytosis, T-cell deficiency, inhibition of the phagocyte absorption function of the 3 rddegree (Amano and Shimizu 2014).…”
Section: Cystitismentioning
confidence: 99%